Bioprospecting and Chemical Potential of Bioactive Compounds of Medicinal Plants of the Baduy Tribe of Banten Province - saefurohman, Asep saefurohman; Arfi, Angger; Ais, Ais; Fahrizal, Fahrizal (Jurnal Kimia Fullerene, 2025)
Bioprospecting is the exploration, collection, research, and utilization of genetic and biological resources to obtain chemical compounds, genes, organisms, and other natural products. Bioprospection of medicinal plants is an exploration activity to have added value from both a scientific and an economic perspective. Indonesia is one of the archipelago countries that has the potential for cultivating various plants. The objective of this research was to find bioactive compounds from plants in Baduy and the chemical potential of bioactive compounds as drugs. White Ginger (Curcuma zedoria Rosc) is included in the family of medicinal plants (TOGA) is a plant in the family Zingiberaceae. This plant is widely found in Baduy. The method used in this research is descriptive qualitative, by describing the quality of bioactive compounds contained in traditional medicinal plants in the Baduy tribe. The research results showed that the yields obtained from the extraction using 70% ethanol solvent, water, and steeping water of white rhizome powder were 24.51%, 9.65%, and 12.22%, respectively. 70% ethanol medicinal plant extract and hot water at a concentration of 300 ppm did not have an inhibitory power on the activity of the enzyme tyrosine kinase, while the crude extract of 300 ppm aquadest had an inhibitory power of 7.23%. At a higher extract concentration, which is 700 ppm, 70% ethanol extract has the highest inhibitory power of 27.77%. The inhibition power of 700 ppm aqueous extract is 26.13% and 700 ppm hot water extract is 24.50%.